Numerical Study of Three-Dimensional Flow Characteristics in Isolation Rooms with Negative Pressure Differences - Wawan Aries Widodo; Satryo Fadhian Shidqi Nugroho (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2023)
This paper will discuss computational fluid dynamics (CFD) modeling regarding a patient isolation room design with negative pressure. This model was made after conducting independence tests and validation data on several existing room designs. The room design is simulated with variations in pressure differences -2.5 Pa, -5 Pa, -8 Pa, and -15 Pa, respectively, and variations in the position of one bed and two beds. The results show that the stagnation flow that occurs in the isolation room with a two-bed configuration is a lot happens and in a dangerous position than the stagnation flow that occurs in the isolation room with a one-bed configuration. The greater the pressure difference used, the more uniform the pressure in the room. The conclusion is that the distribution of pressure difference variations has the same trend on the velocity and temperature distribution graph, then the pressure difference variation of -15 Pa has the best pressure distribution. Variations in bed position configuration affect the characteristics of airflow in the room. The velocity, pressure, and temperature along the bed are still within the patient's comfort limit.